Analisis Strategi Pemasaran pada Toko Ayu Cosmetics di Bumyagara Mustikajaya dalam Usaha Peningkatan Pendapatan Penjualan - Mira Anggaina; Hadita Hadita (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
There are many challenges faced by business people, namely technological developments and unpredictable conditions such as the Covid-19 pandemic. Since the outbreak, all fields have demanded to be digital. Business people can use this to carry out online marketing. This research aims to analyze the marketing strategy at the Ayu Cosmetics Store in Bumyagara Mustikajaya in an effort to increase sales revenue before and after the Covid-19 pandemic. The approach taken is a qualitative description method in the form of interviews with shop owners, observations, and literature studies to support research data. It was found that even though it has not used online marketing, Toko Ayu Cosmetics can still survive by relying on several salons that it subscribes to, and the ability of the owner who continues to want to learn and understand the market situation. So the next online marketing strategy that will be implemented is to use digital/e-commerce platforms such as Shopee which focuses on selling beauty salon products.